Trash into Treasure: Building Up by Throwing Out in Chongoyape, Peru - Montalvo, Tina (2015)
In a town in northern Peru, a community has stuffed trash into 7,000 half-liter plastic bottles, also known as eco-bricks, and built a library. The town has no sanitary landfill and little knowledge of trash management. Yet residents have managed to create Peru’s first eco-brick building out of one metric ton of inorganic garbage, an accomplishment that owes its success to community participation and the cooperation of many organizations.